Evaluating the Role of Promotion in Enhancing Healthcare Services: A Review - Bangera, Prince James S; Manjunath Kuntoji; Morageri Mubintaj; Deepika Ravi (Jurnal Vokasi Kesehatan, 2024)
This article evaluates the role of promotion in enhancing healthcare services by reviewing the historical context and development of marketing in the healthcare industry, which began in the early 1970s. The primary objective of this article is to understand how promotion and marketing have become vital components in hospital and healthcare management. The method used is a review of various published articles to explore the challenges, opportunities, and the impact of marketing on the emotional relationship between healthcare providers and patients, as well as its influence on customer engagement, trust, and loyalty. The findings of this article indicate that promotion and marketing methods have a positive impact on improving healthcare service quality and achieving a competitive edge, particularly through digital marketing and effective brand equity management.